(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current study finds its root at Kotulpur block of Bankura district in west Bengal. The study mainly tries to reveal the impact of Kanyashree at a time grant in the life of its direct beneficiaries. By constructing the sample size with 100 respondents the study makes an attempt to verify the truth behind the scenario. Accordingly, the study ends with plenty of serious information regarding the implementation as well as the effectiveness of the particular scheme. As far as women empowerment is concerned several motivational factors work together to broaden the efficacy of the aforementioned grant. Eventually, it is concluded that different educational and career centric approaches basically construct a new arena of women empowerment. According to the study, Kanyashee grant as a financial push from outside has been playing an important role in building up their self-esteem and self-dependency as well.